Towards an "Invested Empirical Method": Reclaiming Feminist Science Studies - Scott-Dixon, Krista (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This article summarizes some of the contributions of feminist science scholars in order to explore the possibilities of a critical science of sex, gender, and sexuality, and suggests the radical possibilities of "invested empirical research methods" - investigative approaches grounded in both scientific method and an interest in social justice.